2018
DOI: 10.3389/fncel.2018.00485
|View full text |Cite
|
Sign up to set email alerts
|

TRH Analog, Taltirelin Protects Dopaminergic Neurons From Neurotoxicity of MPTP and Rotenone

Abstract: Dopaminergic neurons loss is one of the main pathological characters of Parkinson’s disease (PD), while no suitable neuroprotective agents have been in clinical use. Thyrotropin-releasing hormone (TRH) and its analogs protect neurons from ischemia and various cytotoxins, but whether the effect also applies in PD models remain unclear. Here, we showed that Taltirelin, a long-acting TRH analog, exhibited the neuroprotective effect in both cellular and animal models of PD. The in vitro study demonstrated that Tal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Then, one-way analysis of variance (ANOVA) followed by least significant difference (LSD) post-hoc comparisons for multiple groups comparisons were conducted (more than two groups) (Zheng et al, 2018). Paired samples T test for comparing extracellular glutamate concentrations before and after LY354740 injection (Table 1 for details).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Then, one-way analysis of variance (ANOVA) followed by least significant difference (LSD) post-hoc comparisons for multiple groups comparisons were conducted (more than two groups) (Zheng et al, 2018). Paired samples T test for comparing extracellular glutamate concentrations before and after LY354740 injection (Table 1 for details).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral assessments were performed as our previously described and conducted at 10:00 am on each testing days (Zheng et al, 2018). Each group contained eight mice.…”
Section: Behavioral Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Pathological studies of several rare hereditary parkinsonism cases found no Lewy body or deposition of α-synuclein (5). However, the main neuropathological features of PD are the progressive loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc) (6). Sporadic PD is also characterized by the presence of Lewy bodies and Lewy neurites, which consist primarily of misfolded and aggregated protein α-synuclein in the remnant neurons (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%